Answer:
[tex](x^{-3} )^{2}[/tex]
[tex]x^6 x^{-12}[/tex]
Step-by-step explanation:
[tex](x^{3} x^{-6} )^{2}[/tex] is the expression given to be solved.
First of all let us have a look at 3 formulas:
[tex]1.\ p^a \times p^b = p^{(a+b)}\\2.\ (p^a \times q^b)^c = (p^{a})^c \times (q^{b})^c\\3.\ (p^a)^b = p^{a\times b}[/tex]
Both the formula can be applied to the expression([tex](x^{3} x^{-6} )^{2}[/tex]) during the first step while solving it.
Applying formula (1):
[tex](x^{3} x^{-6} )^{2}[/tex]
Comparing the terms of [tex](x^{3} x^{-6} )[/tex] with [tex]p^a \times p^b[/tex]
[tex]p=x, a =3, b=-6[/tex]
[tex]\Rightarrow x^{3+(-6)}\\\Rightarrow x^{3-6}\\\Rightarrow x^{-3}[/tex]
So, [tex](x^{3} x^{-6} )^{2}[/tex] is reduced to [tex](x^{-3} )^{2}[/tex]
Applying formula (2):
Comparing the terms of [tex](x^{3} x^{-6} )^{2}[/tex] with [tex](p^a \times q^b)^c[/tex]
[tex]p=q=x, a =3, b=-6, c=2[/tex]
[tex]\Rightarrow (x^{3})^2\times (x^{-6})^2\\\text{Applying Formula (3)}\\x^6 x^{-12}[/tex]
So, [tex](x^{3} x^{-6} )^{2}[/tex] is reduced to [tex]x^6 x^{-12}[/tex].
So, the answers can be:
[tex](x^{-3} )^{2}[/tex]
[tex]x^6 x^{-12}[/tex]